2011
DOI: 10.4049/jimmunol.1001348
|View full text |Cite
|
Sign up to set email alerts
|

The TLR7 Agonist R848 Alleviates Allergic Inflammation by Targeting Invariant NKT Cells To Produce IFN-γ

Abstract: It has been documented that TLR7 stimulation triggers not only antiviral responses, but also alleviates experimental asthma. Considering the implication of invariant NKT (iNKT) cells in both situations, we postulated that they might contribute to the anti-inflammatory effect of TLR7 ligands. We show in this study that spleen cells activated by the TLR7 agonist resiquimod (R848) attenuate allergic inflammation upon adoptive transfer when they are recovered from wild-type, but not from iNKT cell-deficient Jα18−/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
45
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 33 publications
(40 reference statements)
8
45
0
Order By: Relevance
“…In a murine asthma model, intranasal application of R848 efficiently inhibited the asthma phenotype, including airway hyperreactivity (AHR), airway inflammation, mucus hypersecretion, and Th2 cytokine production, confirming findings of previous studies in asthma models (18,(23)(24)(25)(26). Furthermore, R848 strongly induced IL-27 secretion, which was crucial for its therapeutic effect as demonstrated by in vivo neutralization of IL-27 via an mAb.…”
supporting
confidence: 67%
See 3 more Smart Citations
“…In a murine asthma model, intranasal application of R848 efficiently inhibited the asthma phenotype, including airway hyperreactivity (AHR), airway inflammation, mucus hypersecretion, and Th2 cytokine production, confirming findings of previous studies in asthma models (18,(23)(24)(25)(26). Furthermore, R848 strongly induced IL-27 secretion, which was crucial for its therapeutic effect as demonstrated by in vivo neutralization of IL-27 via an mAb.…”
supporting
confidence: 67%
“…It activates APCs via the MyD88 pathway, leading to induction of proinflammatory cytokines and chemokines, especially large amounts of type 1 IFNs (22). In different rodent models of experimental asthma, R848 effectively inhibited the development of asthma and even reversed already established asthma symptoms after systemic and intranasal application (18,(23)(24)(25).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In agreement with this notion, we have recently shown that R848-induced NKT cell activation alleviates asthma symptoms through IFN-g production in an IL-12-dependent manner [27]. The present study shows that CD25 depletion reverses the effect of R848 on all asthma hallmarks tested, namely AHR, cellular infiltration in BALF and production of Th2 cytokines (IL-4, IL-5, IL-10, and IL-13) as well as chemokines (eotaxin) and the Th17 cytokine IL-17.…”
Section: Discussionsupporting
confidence: 64%